2012
DOI: 10.4314/ajpsy.v15i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma homocysteine in association with decreased vitamin B12, folate, serotonin, lipids and lipoproteins in depressed patients

Abstract: Objective: Increased plasma homocysteine, decreased vitamin B12 and folic acid levels have been implicated in depressive mood. Plasma homocystine, vitamin B12, folic acid tryptophan, lipids and lipoproteins were determined in depressed patients and controls. Method: Sixty subjects consisting of 30 depressed patients and 30 apparently healthy volunteers, who served as controls, were selected for this study. Anthropometric indices and biochemical parameters were determined using standard procedures. Results: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
2
15
0
1
Order By: Relevance
“…Such an interrelationship between these three substances has been shown in multiple studies performed in patients with various conditions including mood disorders [2,16] and has been by some authors regarded as a rationale for supplementation with folic acid or vitamin B 12 for the treatment of depression. However, no direct relationship between improvement of depression and a reduction of HCY level was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an interrelationship between these three substances has been shown in multiple studies performed in patients with various conditions including mood disorders [2,16] and has been by some authors regarded as a rationale for supplementation with folic acid or vitamin B 12 for the treatment of depression. However, no direct relationship between improvement of depression and a reduction of HCY level was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the largest sample examined to date including 11,757 participants, Gu et al [1] found a significant positive relationship between elevated serum HCY levels and currently experiencing depressive symptoms. Since a significant correlation between higher HCY levels and lower vitamin B 12 and folic acid in depressed patients was observed [2], it may be proposed that both vitamin B 12 and folic acid can be regarded as elements of the HCY system. Procedures aiming at lowering HCY such as supplementation with either folic acid or vitamin B 12 have been suggested for the treatment of depression.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 140 individuals with symptoms of depression were shown to have significantly low levels of plasma pyridoxal phosphate, the phosphate derivative of vitamin B6 [96]. Furthermore, patients suffering from depression have elevated plasma homocysteine levels, which correlate with low vitamin B6 and folate levels [112].…”
Section: Vitamin B6 (Pyridoxine)mentioning
confidence: 99%
“…The methioninehomocysteine metabolic pathway intermediaries, S-adenosylmethionine and S-adenosylhomocysteine, produce methyl groups required for the synthesis of catecholamines and DNA methylation. Since Hcy is a sensitive indicator of vitamin B defi ciency, an elevated Hcy level has been suggested as a marker for a pathogenic process (102) . Recent reports on Hcy measured in AH, plasma, and tear fl uid have yielded mixed results with some studies demonstrating an association with normal tension glaucoma, pseudoexfoliative glaucoma, and POAG, whilst others have not (101,103) .…”
Section: Homocysteinementioning
confidence: 99%